International Conference on Industry 4.0 for Agri-food Supply Chains: Addressing Socio-economic and Environmental Challenges in Ukraine - Trollman, Hana; Samoilyk, Iuliia (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Engineering Proceedings reprint is focused on how Industry 4.0 technologies may benefit agri-food supply chains by alleviating socio-economic and environmental challenges. The evolving interdisciplinary research is motivated by aiding Ukraine in the war against Russia.